Numerical Simulation of the Transitional and Unsteady Flow through a Low Pressure Turbine - Romuald Skoda; Rudolf Schilling; Meinhard T. Schobeiri (International Journal of Rotating Machinery)
A simulation strategy is developed for the computation of the time-accurate flow through low pressure turbines with periodically impinging wakes generated by moving cylinder rods. For the simulations, different time steps and turbulent inflow conditions and their impact on the laminar separation on the suction side are considered. A realizable cubic low-Reynolds number k-ɛ turbulence model and a linear V2F model are utilized to capture transitional effects, in particular the laminar separation bubble at the suction side. For comparison with experimental data, published in a companion paper, pressure distribution and boundary layer profiles of the mean and fluctuation RMS velocity are considered. While the periodically disturbed flow is predicted with a reasonable accuracy by each model, for the undisturbed flow, an additional realizability condition based on a turbulent time scale bound is incorporated into the cubic model in order to capture the reattachment of the flow.